Towards a plan of actions for mankind :mason Volume 5: conclusion and perspectives - Marois, M.; Institut de la vie. (Oxford : Pergamon Press, 1974)
This book contained proceedings prepared for the world conference sponsored by the Institut de la vie.
English or French.
Includes bibliographies.
lje 19/4/18
Loans
Keywords: Environmental policy; Economic development; Human ecology